Association of Estrogen Receptors with Polycystic Ovary Syndrome and Subsequent Infertility in Affected Patients - Anees Fatima, Shirin Gul Suhail, Uzma Zia, Rana Abid Ali, Maryam Raana, Tania Naveel, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic ovarian syndrome (PCOS) is the reproductive and metabolic abnormality of females characterized by delayed folliculogenesis, hyperandrogenism, and multiple ovarian cysts, associated with an increased risk of infertility, abortion and endometrial cancer. Objectives: Therefore, the effects of estrogen receptors on PCOS incidence were investigated through quantification of ER-α and ER-β mRNAs expressions via RT-PCR. Study Design: This cross-sectional study was executed at Mayo Hospital Lahore, from January-2021 to September-2022, including 320 participants. Methods: 180 females enrolled in this study were diagnosed with PCOS. ER-α and ER-β were isolated and amplified separately on RT-PCR for their quantification. Results: It was found that expression of tER-α mRNA did not differ between size-matched normal and PCOS follicles, and the concentration of both types of nitrogenous bases, GC and TC, was equivalent. Yet, ER-β mRNA expression was substantially higher in TC (p<0.05) than in GC. Conclusion: It was concluded that PCOS is the major cause of infertility among Pakistani women. It is mostly curable if identified accurately. Established on ER and haplotype data, genetic coding for ER-α and ER-β mRNA are good markers for determination of the association of estrogen receptors with PCOS. Keywords: Endocrine disorder; Estrogen receptors; Genetic coding; Infertility.